From sustainability transitions to security: Mapping the new terrain for innovation policy - Paula Kivimaa; Matthijs Janssen; Jakob Edler (Fraunhofer Institute for Systems und Innovation Research ISI, 2026)
Increasing rise of military and non-military security issues, globally, influences innovation policies and interacts with policy aspirations to address societal challenges, notably around sustainability transitions. Drawing from research on security, geopolitics, and transformative and mission-oriented innovation policy, we map out what an increased focus on security means for challenge-led innovation policymaking. The analysis is structured around five policy imperatives: directionality, experimentation, inclusivity, regime destabilisation, and policy mix adaptation. Some clear synergies exist between sustainability and security, e.g., directing innovation support towards technologies that reduce supply chain dependencies, or dual-use technologies that improve resource efficiency and defence capability. Tensions also exist, e.g. security-risks of smart 'clean' technologies, or making innovation processes more closed for security reasons. Three broad policy strategies to govern the interrelations between security and sustainability objectives in innovation policy are proposed. The contribution raises awareness and provides nuance regarding ways the rising security concerns influence challenge-led innovation policy.
Keywords: 330; sustainability transistions; security; innovation policy